Governance of sustainable development: Towards synergies between corporate and political governance strategies - Raimund Bleischwitz (Wuppertal Institut für Klima, Umwelt, Energie, 2003)
The paper explores a framework for analysing governance towards sustainabledevelopment. Departing from the thesis about a possible positive role forcorporate action, it refers to recent theorizing about both market and governmentfailures. Discussing externalities, public goods, information and adaptationdeficits, as well as bureaucracies' self-interest, corruption and capture of theregulator, the paper stresses the importance of governance aiming at synergiesbetween corporate and political governance. Concerning framework conditions, itoutlines principles of regulated self-regulation. Following the thesis about apositive role, the paper adds recent insights about theories of the knowledge-basedfirm, which help to analyse market evolution. In this context, it outlines theconcept of responsible corporate governance. Because governance involvesactors in their daily operations and certainly goes beyond setting a frame, thepaper finally discusses innovation-inducing regulation, serving complementaryfunctions to a framework and business operations. The conclusion is drawn thatgovernments' main function is to facilitate learning processes, thus departing fromstates' function as known from welfare economics. Thus, governance will have tobe explored as collective learning, involving business, governments, and civilsocieties' actors. – – Der Beitrag entwickelt einen Analyserahmen für einige Steuerungsfragen, die füreine zukunftsfähige Entwicklung relevant sind. Im Mittelpunkt steht die Suchenach Strategien zur Aktivierung von Unternehmen, Märkten und Zivilgesellschaft.Zunächst werden Theorien des Markt- und Staatsversagens analysiert; in beidenBereichen erlaubt der Stand der Forschung eine Überwindung der Gegenüber-stellung (hier der Markt, dort der Staat) und eine Hinwendung zu komplexerenGovernance-Strukturen. Derartige Governance-Strukturen werden im Beitrag ent-wickelt. Das Papier erläutert das Anliegen einer regulierten Selbstregulierung. Esanalysiert neuere Unternehmens- und Marktprozesstheorien und stellt Prinzipeneiner verantwortlichen Unternehmensführung vor. Im letzten Abschnitt geht esauf verbleibende Politikspielräume ein, die unter den Stichworten Aktivierungvon Innovationen und responsive Regulierung diskutiert werden. Die Schluss-folgerung lautet, dass Politik zunehmend als kollektiver Lernprozess analysiertwerden muss, in dem Anreize für die dezentrale Wissensgenerierung durchprivate Akteure zu entwickeln sind. Funktionen des Staates, wie sie etwa noch inder Wohlfahrtsökonomie formuliert werden, werden dadurch zugunstenevolutorischer Ansätze relativiert.
urn:nbn:de:bsz:wup4-opus-17337
Keywords: 330; Nachhaltige Entwicklung; Theorie; Governance-Ansatz